Going to Extremes of Lung Physiology–Deep Breath-Hold Diving - Tetzlaff, Kay; Lemaitre, Frederic; Burgstahler, Christof; Luetkens, Julian A.; Eichhorn, Lars (Frontiers in Physiology, 2021)
Breath-hold diving involves environmental challenges, such as water immersion, hydrostatic pressure, and asphyxia, that put the respiratory system under stress. While training and inherent individual factors may increase tolerance to these challenges, the limits of human respiratory physiology will be reached quickly during deep breath-hold dives. Nonetheless, world records in deep breath-hold diving of more than 214 m of seawater have considerably exceeded predictions from human physiology. Investigations of elite breath-hold divers and their achievements revised our understanding of possible physiological adaptations in humans, and revealed techniques such as glossopharyngeal breathing as being essential to achieve extremes in breath-hold diving performance. These techniques allow elite athletes to increase total lung capacity and minimize residual volume, thereby reducing thoracic squeeze. However, the inability of human lungs to collapse early during descent enables respiratory gas exchange to continue at greater depths, forcing nitrogen (N2) out of the alveolar space to dissolve in body tissues. This will increase risk of N2 narcosis and decompression stress. Clinical cases of stroke-like syndromes after single deep breath-hold dives point to possible mechanisms of decompression stress, caused by N2 entering the vasculature upon ascent from these deep dives. Mechanisms of neurological injury and inert gas narcosis during deep breath-hold dives are still incompletely understood. This review addresses possible hypotheses and elucidates factors that may contribute to pathophysiology of deep freediving accidents. Awareness of the unique challenges to pulmonary physiology at depth is paramount to assess medical risks of deep breath-hold diving.